2005
DOI: 10.1002/bdra.20120
|View full text |Cite
|
Sign up to set email alerts
|

The importance of appropriate controls, animal feed, and animal models in interpreting results from low-dose studies of bisphenol A

Abstract: Interpreting results of studies that report only negative effects is problematic. A number of published studies to determine whether chemicals with estrogenic activity can cause effects at low doses have not taken into account the possibility that the commercial animal feed being used can mask effects of even potent estrogenic drugs such as diethylstilbestrol (DES). In addition, the sensitivity of the strain of animal being used for the specific category of chemical being tested has not always been described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…In addition to the route of administration, it is imperative that consistent environmental conditions be used to assess BPA impact on carcinogenesis in laboratory animals [98]. Specifically, care should be taken to minimize exposure to polycarbonate caging and plastic water bottles, an established source of BPA [25].…”
Section: Summary and Recommendations For Future Studiesmentioning
confidence: 99%
“…In addition to the route of administration, it is imperative that consistent environmental conditions be used to assess BPA impact on carcinogenesis in laboratory animals [98]. Specifically, care should be taken to minimize exposure to polycarbonate caging and plastic water bottles, an established source of BPA [25].…”
Section: Summary and Recommendations For Future Studiesmentioning
confidence: 99%
“…The animal species and diets are of great importance (26,30). Several studies demonstrated that some commonly used outbred rats and mice are less responsive to oestrogenic substances than certain inbred mouse and rat strains, at various oestrogensensitive endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the uterotrophic assay performed on the immature model was shown to be more sensitive to an increase in uterine weight evoked by oestrogenic compounds than the model of ovariectomised animals (17). In both versions the baselines for negative and positive controls are necessary for a rational interpretation of the results (19,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, besides the appropriate animal model and control groups (negative and positive), feed is of significant importance in interpreting results of the studies on endocrine disruptors (EDs) (1,2,31). Selection of the most appropriate diet for ED research conducted on rodent experimental models, is not only a current subject providing the current proposals to mass screen a wide range of endocrine-disrupting compounds (EDCs), but it is also a decision that should be put under a serious consideration before standardising or initiating such studies (29).…”
Section: Introductionmentioning
confidence: 99%